Implementasi Fetch API dalam pengembangan Backend Website Daftar Film dengan Next.JS - Maulana, Irvan Dhimas; Susetyo, Yeremia Alfa (LPPM STIKOM Tunas Bangsa, 2025)
This study aims to improve the performance of a film list website by implementing the Next.JS framework along with its Fetching API to solve challenges in search efficiency and providing accurate and up-to-date information for users. The amount of outdated and irrelevant data on film websites often prevents users in finding current movie information. This research develops an application using Next.JS, integrated with the Fetch API, to dynamically retrieve data using Server-Side Rendering (SSR) and Static Site Generation (SSG), improving communication between server and client, while providing a responsive and SEO-friendly user experience. Testing results with Lighthouse and Chrome DevTools show improved performance, with an application score of 92 on the Vercel platform and 82 on the Local side. Cache optimization on Vercel also reduced data transfer size from 2.2 MB to 0.27 MB, significantly speeding up load times and stabilizing the application. These results indicate that the application successfully delivers relevant and up-to-date information with high speed and stable performance. However, this study is limited in terms of testing devices and focuses only on the Vercel hosting platform.